The Economics and Policy Implications of Infrastructure Sharing and Mutualisation in Africa - Marino Garcia, Jose; Kelly, Tim (World Bank, Washington, DC, 2016)
Infrastructure sharing is one of the main trends in broadband infrastructure deployment. In developing countries, particularly in sub-Saharan Africa, there is a trend for governments to back infrastructure sharing projects as a way to reduce costs in network deployments, expand coverage, reduce the rural-urban digital divide, and accelerate broadband take-up. Traditional infrastructure sharing models, such as regulated access to the so-called “last-mile” network or site sharing agreements among mobile operators, have given way in recent times to new designs. The mutualisation model, where a common facility is operated by all market participants, and the cooperative model, where the telecommunication infrastructure is housed or jointly constructed with other linear infrastructures, are the two most popular designs.